+0  
 
0
123
1
avatar

If (w + 13)^2 = (3w + 7)(2w + 5), solve for w.

 Jan 24, 2022
 #1
avatar+565 
-1

First we open parenthesis.

\(w^2 + 26w + 169 = (3w + 7)(2w + 5)\)

 

Then we open parenthesis on the right side of the equation.

\(w^2 + 26w + 169 = 6w^2 +29w + 35\)

 

Then we have to combine like terms.

\(5w^2 + 3w -134 = 0\)

 

Now we can use the quadratic formula: w = \(-b {+\over} \sqrt{b^2 - 4ac}\over2a\) where a is the coefficient of \(w^2\), b is the coefficient of w, and c is the constant.

Now to plug in the values into the formula: we get

w = \(-3 {+\over}\sqrt{2689}\over10\)

 

 

smiley

 Jan 24, 2022

17 Online Users

avatar